2013
DOI: 10.1016/j.stem.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Embedded Osteocytes Regulate Mobilization of Hematopoietic Stem/Progenitor Cells

Abstract: The bone marrow (BM) niche comprises multiple cell types that regulate hematopoietic stem/progenitor cell (HSPC) migration out of the niche and into the circulation. Here, we demonstrate that osteocytes, the major cellular component of mature bone, are regulators of HSPC egress. Granulocyte colony-stimulating factor (G-CSF), used clinically to mobilize HSPCs, induces changes in the morphology and gene expression of the osteocytic network that precedes changes in osteoblasts. This rapid response is likely under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 38 publications
1
142
0
1
Order By: Relevance
“…Interestingly, exogenous osteocalcin rescued only the diabetic phenotype but not fat loss in this model. 51 Together with the fact that osteocalcin is highly expressed not only in osteoblasts but also in osteocytes, 40 and with our observations on OL mice in which glucose metabolism is not altered, but fat loss is prominent, mesenchymal lineage cells may control finely the energy metabolism depending on their differentiation stages. Moreover, osteoblasts and osteocytes may regulate preferentially glucose and fat metabolisms, respectively (Figure 4).…”
Section: Role Of Osteocytes For Remote Organssupporting
confidence: 56%
See 2 more Smart Citations
“…Interestingly, exogenous osteocalcin rescued only the diabetic phenotype but not fat loss in this model. 51 Together with the fact that osteocalcin is highly expressed not only in osteoblasts but also in osteocytes, 40 and with our observations on OL mice in which glucose metabolism is not altered, but fat loss is prominent, mesenchymal lineage cells may control finely the energy metabolism depending on their differentiation stages. Moreover, osteoblasts and osteocytes may regulate preferentially glucose and fat metabolisms, respectively (Figure 4).…”
Section: Role Of Osteocytes For Remote Organssupporting
confidence: 56%
“…22 In our subsequent study, the cellular connection between endosteal osteoblasts and boneembedded osteocytes had been disrupted after G-CSF treatment. 40 However, osteolineage cells do not express G-CSF receptor. 22 As osteocytes express b2-adrenergic receptor, and surgical denervation disrupts the regulation of osteocyte specific genes, it is confirmed that osteocytes are regulated by the SNS.…”
Section: Contribution Of Osteocytes In Endosteal Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of important roles for osteocytes in bone biology, such as mechanosensation and mineral metabolism, have been identified in previous studies [11]. A series of recent studies, including one by our group, has revealed the importance of osteocytes in the regulation of hematopoiesis [12][13][14]. In this review, we provide an overview of advances in our knowledge of regulatory mechanisms in the hematopoietic system by osteolineage cells in the endosteal area.…”
Section: Introductionmentioning
confidence: 93%
“…G-CSF increases sympathetic tone and eliminates endosteal macrophages, which also causes alteration of the HSC/HPC niches. In a recent study, our group assessed osteocyte function in regulating HSC/ HPC mobilization induced by G-CSF [13]. Analysis of gene expression profile of osteoblasts and osteocytes in mice during G-CSF treatment revealed that osteocytes are suppressed by G-CSF treatment in the same manner as osteoblasts.…”
Section: Role Of Osteocytes For the Mobilization Of Hscs/hpcsmentioning
confidence: 99%